The Influence E-WOM And Brand Image On Repurchase Intention Through Consumer Trust In ESQA Cosmetics Products In Pekanbaru - Ine Safanah; Zulkarnain Zulkarnain; Jushermi Jushermi (Westscience Press, 2025)
This study aims to determine the effect of Electronic Word of Mouth (E-WOM) and Brand Image on Repurchase Intention of ESQA cosmetic products in Pekanbaru City, as well as the role of Consumer Trust as an intervening variable. The population in this study consists of people in Pekanbaru City aged 17 to 40 years who have purchased, used, and intend to repurchase ESQA cosmetic products. The sampling in this study was conducted using a purposive sampling technique and the Hair formula, resulting in a total of 130 respondents. The data analysis method used in this study is Structural Equation Modeling - Partial Least Square (SEM-PLS) with SmartPLS version 4.1.1.4 software. The results show that Electronic Word of Mouth (E-WOM) has a significant effect on Repurchase Intention and Consumer Trust in ESQA cosmetic products in Pekanbaru City. Brand Image does not have a significant effect on Repurchase Intention but has a significant effect on Consumer Trust. In addition, Consumer Trust is proven to have a significant effect on Repurchase Intention. Maximizing the Electronic Word of Mouth (E-WOM) strategy through the use of social media and positive consumer reviews to enhance trust in the brand. Considering that Consumer Trust has been proven to be a key factor in driving Repurchase Intention, companies need to build stronger relationships with consumers through product transparency, consistent quality, and responsive service. Furthermore, although Brand Image does not directly affect Repurchase Intention, improving Brand Image remains important to strengthen consumer trust, which in turn can foster sustainable repurchase intentions.